Analysis of The Merger of PT Bank Syariah Indonesia in Legal and Sharia Perspective - Khotibul Umam; Vina Berliana Kimberly (Universitas Negeri Semarang, 2022)
Legal analysis are necessary to the general considerations for merging in order to create a national banking industry structure that is strong and competitive and responsive to future challenges and special considerations for the merger of PT BNI Syariah and PT Bank Syariah Mandiri into PT Bank Syariah Indonesia, namely as an effort to create new and contributing national development workers. Towards the welfare of the wider community and shows the performance of sharia banking in Indonesia which is modern, universal, and provides goodness for all nature (Rahmatan Lil ‘Aalamiin). This issue has significance to be studied based on law and sharia because it can be a legal reference in the future. The research was conducted based on normative legal research and qualitative analysis. The result of this research shows that the considerations and the merger process are based on statutory regulations and have complied with sharia principles in the sense of fulfilling the values and objectives of Islamic banks, as well as being in line with the function of law as a means of development in order to achieve the benefit of the people and all the people of Indonesia.